Global sharing of COVID-19 therapies during a "New Normal" - Jecker, NS; Atuire, CA (Wiley, 2022)
This paper argues for global sharing of COVID-19 treatments during the COVID-19 pandemic and beyond based on principles of global solidarity. It starts by distinguishing two types of COVID-19 treatments and models sharing strategies for each in small-group scenarios, contrasting groups that are solidaristic with those composed of self-interest maximizers to show the appeal of solidaristic reasoning. It then extends the analysis, arguing that a similar logic should apply within and between nations. To further elaborate global solidarity, the paper distinguishes morally voluntary, sliding-scale, and mandatory versions. It argues for an all-hands-on-deck approach and gives examples to illustrate. The paper concludes that during the COVID-19 crisis, global solidarity is a core value, and global sharing of COVID-19 treatments should be considered a duty of justice, not of charity.